Geopolitical Risk, Foreign Direct Investment, and Renewable Energy Consumption in OECD Countries - Le, Thi Bich Hop (Unisia, 2025)
This study examines how geopolitical risk shapes renewable energy consumption in Organisation for Economic Co-operation and Development countries, with particular attention to the mediating role of foreign direct investment. Against a backdrop of rising global geopolitical tensions and growing energy security concerns, the article aims to clarify whether geopolitical risk ultimately accelerates or constrains the transition toward renewable energy in advanced economies. Using a balanced panel of twenty-three Organisation for Economic Co-operation and Development countries over the period 2000–2024, the analysis applies second-generation panel econometric techniques that account for cross-sectional dependence, non-stationarity, and long-run relationships. The empirical strategy combines cointegration tests, fixed effects estimation, and instrumental variable approaches to address endogeneity, alongside a mediation framework to evaluate the role of foreign direct investment. The results provide robust evidence of a long-run relationship between geopolitical risk and renewable energy consumption. Higher geopolitical risk is found to exert a positive and statistically significant effect on renewable energy consumption, indicating that heightened uncertainty encourages diversification away from fossil fuels toward renewable energy sources. Moreover, geopolitical risk is shown to increase foreign direct investment inflows into Organisation for Economic Co-operation and Development countries, which in turn further supports renewable energy consumption, confirming the presence of an indirect transmission channel. These findings remain stable across alternative measures of geopolitical risk and multiple robustness checks. Overall, the study concludes that geopolitical risk can act as a catalyst rather than a barrier to sustainable energy transition in advanced economies. The results highlight the importance of stable investment environments and proactive energy policies that leverage foreign direct investment to strengthen renewable energy deployment under conditions of global uncertainty.